PENGARUH IMPLEMENTASI SUPERVISI KLINIS KEPALA SEKOLAH TERHADAP MOTIVASI KERJA DAN KINERJA GURU DI SEKOLAH MENENGAH PERTAMA (SMP) NEGERI 2 ADIANKOTING - Roland Sucipto Sinambela; Hisardo Sitorus; Taripar Arifin Samosir (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The purpose of this study was to determine 1) the extent to which the implementation of the principal's clinical supervision influences the work motivation of teachers at SMP Negeri 2 Adiankoting; 2) the extent to which the implementation of the principal's clinical supervision influences the performance of teachers at SMP Negeri 2 Adiankoting; and 3) the effect of the principal's clinical supervision on the work motivation and performance of teachers at SMP Negeri 2 Adiankoting. The method used in this study is a quantitative method with a causal approach. The population is 30 teachers at SMP Negeri 2 Adiankoting, and this study is a population study determined using a saturated sampling technique. The instrument trial was conducted on 30 people outside the research sample so that it was known that all research instruments were declared valid and reliable because they had met the criteria for validity and reliability values. Data were collected with a closed questionnaire of 217 items. The results of the data analysis show that: 1) sig. <0.05, namely 0.000 <0.05, thus it is known that there is a positive and significant influence of the implementation of the principal's clinical supervision on teacher work motivation at SMP Negeri 2 Adiankoting; 2) sig. <0.05, namely 0.005 <0.05, thus it is known that there is a positive and significant influence of the implementation of the principal's clinical supervision on teacher performance at SMP Negeri 2 Adiankoting; and 3) sig. <0.05, namely 0.004 <0.05, thus it is known that there is a positive and significant influence of the implementation of the principal's clinical supervision on teacher work motivation and teacher performance at SMP Negeri 2 Adiankoting, thus Ha is accepted and H0 is rejected